Estudo da remoção de H2S de biogás sob diferentes condições operacionais utilizando soluções contendo ferro em um sistema em escala de bancada - Angheben, Antonio Augusto (2017)
Biogas is a combustible gaseous mixture obtained from the anaerobic digestion of different types of waste. Since, from your combustion, it is possible to generate thermal and / or electrical energy has been classified as a form of biofuel. Currently, the major producers of this type of biofuel are agro industries. However, due to the composition of the biogas, it is necessary to apply efficient systems for the removal of present H2S and forms of sampling capable of representing the actual composition of the gases. Based on this premise, studies were carried out on sampling for the evaluation of the biogas composition generated in several types of agro industries in the western region of Paraná, and a bench scale purification system was constructed to reduce the concentration of H2S present in biogas. The purification system was operated using two solutions: one containing iron ions and the other with Fe/EDTA (iron/ethylenediaminetetraacetic acid) under different operating conditions. The operational conditions to perform the experimental tests were defined according to a planning of experiments called Central Compound Design (CCD) and Central Rotational Compound Design (CRCD). Experimental purification tests were performed using a biogas produced in the biodigester of a pig slaughterhouse located in the western region of Paraná. The results obtained for the biogas sample forms showed less contamination by atmospheric air with the use of vacutainer tubes. In the experiments for the removal of H2S from the biogas, with the solution containing Fe/EDTA obtained, on average, a removal of 88.80%. For the tests with solutions containing iron ions, on average, a removal of 92.63% was obtained. Although the removal in the solution containing iron ions was expressive, it did not indicate the same capacity of regeneration of the solution containing Fe/EDTA. The proposed purification system proved to be unstable and thus not ideal for large-scale application.